1997
DOI: 10.1074/jbc.272.34.21609
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Increases Macrophage-mediated Modification of Low Density Lipoprotein via a Lipoxygenase-dependent Pathway

Abstract: In summary, these data suggest that Ang II increases macrophage LO activity via AT 1 receptor-mediated mechanisms and this further increases the ability of the cells to generate minimally oxidized LDL. These studies provide a link between hypertension and the associated increased atherosclerosis observed in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(69 citation statements)
references
References 52 publications
(48 reference statements)
2
64
2
1
Order By: Relevance
“…24 -26 Ang II promotes recruitment of inflammatory cells to the vessel wall by inducing the expression of monocyte chemoattractant protein-1. 27 Ang II increases low-density lipoprotein oxidation 28 and by interacting with the Ang II subtype-1 (AT1) receptor on macrophage increases 12/15-lipoxygenase activity, 29 suggesting that it may exacerbate atherosclerosis. Indeed, the present study also demonstrated that Ang II exacerbates atherosclerosis in apoE-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…24 -26 Ang II promotes recruitment of inflammatory cells to the vessel wall by inducing the expression of monocyte chemoattractant protein-1. 27 Ang II increases low-density lipoprotein oxidation 28 and by interacting with the Ang II subtype-1 (AT1) receptor on macrophage increases 12/15-lipoxygenase activity, 29 suggesting that it may exacerbate atherosclerosis. Indeed, the present study also demonstrated that Ang II exacerbates atherosclerosis in apoE-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…38 There is evidence that the lipoxygenase pathway is a mediator of angiotensin II, implicating a role for humoral factors such as angiotensin II in mediating oxidative stress responses in the vessel wall. 39 Thus, activation of lipoxygenase may be a possible mechanism contributing to formation of lipid peroxides and oxysterols. Because probucol was able to inhibit cholesterol oxidation in hypertensive rabbits, this finding provides further evidence for continued studies on peroxidation-mediated vascular effects in hypertensive animals.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide can inhibit transglutaminase activity through nitrosylation of the active-site cysteine (Bernassola et al, 1999;Catani et al, 1998;Melino et al, 1997) or through the reaction of nitric oxide with O 2 է to form peroxynitrite, because cysteine residues are particularly sensitive to oxidation with peroxynitrite (Berlett and Stadtman, 1997). Thus, the generation of oxidant stress from smoking (Pryor et al, 1984;Tully et al, 1969), hyperlipidemia (Ohara et al, 1993), diabetes (Horie et al, 1997;Schmidt et al, 1995), and hypertension (Harrison, 1997;Scheidegger et al, 1997), as well as the health status of the endothelium, which is influenced by these and other risk factors (Harrison, 1997), could modulate TG activity.…”
Section: Tg In Atherosclerosismentioning
confidence: 99%